Faktor-Faktor Yang Memengaruhi Persistensi Laba Dengan Book Tax Difference Sebagai Variabel Moderasi - Devy Rachmawati; Nela Safelia; Wiwik Tiswiyanti (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2025)
This study examines how operating cash flow, liquidity and company size influence the persistence of profits analyzed for mining companies listed on the Indonesia Stock Exchange during 2021 to 2023, by considering the book tax difference with the position of the moderating variable. The quality of earnings is determined not only by the amount of high or low profits, but also by the stability of these profits over a certain period of time. Shareholders' expectations of sustainable profits are based on their ability to provide a more reliable estimate of profit performance in the next period. The purposive sampling method was used to obtain a sample of 32 entities. Secondary data is used as study material, and collection is carried out through documentation. Eviews 12 is software that functions to carry out analysis of existing data. These findings show that operating cash flow and liquidity do not contribute to earnings persistence, while company size shows a positive and significant influence on earnings persistence. Book tax difference is proven to be only relevant as a moderating variable in the relationship between company size and profit persistence, while in the relationship between operating cash flow and liquidity, book tax difference does not play a role in the moderator position.